Case Study: Oral Hygiene Education in Stroke Patients Experiencing Self-Care Deficits at Hospital X - Rizka Aulia Syesharini; Zifriyanthi Minanda Putri; Yuanita Ananda (Jurnal Kesehatan Medika Saintika, 2025)
Stroke patients often experience difficulty performing daily activities, including maintaining oral hygiene, due to muscle weakness and reduced strength. In hospitals, oral hygiene efforts tend to focus on patients with medical devices like feeding tubes, while conscious patients are often overlooked. This issue is worsened by the inconsistency of nurses in providing oral hygiene care and the lack of knowledge among family members on how to perform it in bed. Therefore, education for patients and families is essential. Flipcharts and leaflets can be effective tools, tailored to the patient's condition. This paper aims to provide nursing care through oral hygiene education for Mrs. L, a stroke patient. A case report method was used, involving pre- and post-tests with a questionnaire to assess knowledge and skills, along with oral hygiene status (OHI-S). Education was delivered over 20 minutes using a flipchart, followed by a demonstration from the nurse and a re-demonstration by the family. Results showed improvements: knowledge increased from 73% to 93%, skills from 60% to 93%, and OHI-S improved from 3.16 (poor) to 2.1 (sufficient). It is expected that nurses continue bedside education, and that patients and families can apply oral hygiene practices well.